Pictures As Media To Teach English Language For Young Learners - Ainur Rofiq (Leksikon: Jurnal Pendidikan Bahasa, Sastra, dan Budaya, 2023)
Pictures have been one of the most influential sources, especially, in teaching and learning an unknown language. The use of pictures has great implications for teaching and learning the English language to non-natives. The current study aimed to explore the use of pictures to teach the English language in primary schools.The researchers, following the norms of qualitative research, used class observations and interviews as the tools for data collection. The findings of the study reiterated that the use of pictures in language teaching is quite helpful; however, the teachers under observation, often, did not make use of pictures found in the textbooks to teach the English language. The teachers can make their lectures and classroom activities more lively, interesting, and fruitful by employing the pictures found in the textbooks they use to teach the English language.